Análise exergoeconomica e exergoambienal de um sistema de trigeração usando gás natural e extensão para o uso do biogás de aterro sanitário - Alves, André Filipe Mendes (2020)
The objective of this work was to carry out energy, exergoeconomic and exergoenvironmental analysis of a trigeneration system using natural gas. Also, the work aims to perform experimental tests using biogas from the landfill in João Pessoa - PB in the same trigeneration system. Natural gas, whose flaring is seen as clean, and biogas from landfills, appear as possible sources of energy for Brazil, when considering the generation of electric energy through generator sets, due to the energy potential and for meeting the environmental appeals. In addition to the production of electrical energy, the generator sets release large amounts of heat through the exhaust gases of the internal combustion engine, which, through a trigeneration system, can be recovered to generate cold and heat. The analyzes referring to the experimental results of the trigeneration system using natural gas showed that: the thermal efficiency of the internal combustion engine reaches 36.3%; the higher the air-fuel ratio supplied to the engine, the higher the thermal efficiency and the lower the emission levels; the exergetic costs found for the electricity generated was 39.937 R $ / h, for cold it was 7.075 R $ / h and for heat it was 1.89 R $ / h; the calculated environmental impact rate of natural gas was 2.52 Pts / h, electricity generation 2.49 Pts / h, cold 0.16 Pts / h and heat 0.001 Pts / h. Experimental tests using biogas from the sanitary landfill in João Pessoa - PB in the trigeneration system revealed that: the system requires installations of an electronic system capable of controlling the flow of biogas to the engine and a system for controlling engine speed. The estimates, obtained through simulations using the LandGem method and the experimental results, showed that the maximum production of electricity, cold and heat will happen in the year 2029.